ON THE UPPER PRECAMBRIAN STROMATOLITE STANDARD OF NORTH EURASIA - Semikhatov M.A. (My University, 1980)
Review of the distribution of the U.S.S.R. Upper Precambrian stromatolites in time and space demonstrates an unrepeated and unidirectional change of their assemblages along with distinct lateral differentiation of the systematic composition of coeval assemblages. Such a differentiation was most pronounced during Middle and Late Riphean time.
Keywords: Precambrian; Precambrian; Докембрий